DEVELOPMENT OF ENHANCED IONIC LIQUID MIXED MATRIX MEMBRANES FOR CARBON DIOXIDE SEPARATION FROM METHANE - MOHSHIM, DZETI FARHAH (2015)
The low carbon dioxide (C02)/ methane (CH4 ) separation factor through mixed matrix membranes (MMMs) is due to the lack of C02 affinity towards the membranes and the presence of interfacial voids in the membranes. The main objective of present study is to synthesize the enhanced MMMs (1L3Ms) by incorporating two different types of imidazolium-based ionic liquids (!Ls) into the polyethersulfone (PES) silicoaluminophosphate (SAP0-34) based MMM. This was achieved by blending different concentrations of !Ls at a fixed PES-SAP0-34 mixture. The synthesized membranes were physico-chemically characterized and the performances of these membranes were evaluated in term of permeance and selectivity. The synthesized membranes were found to have dense and voids-free structure with lower polymer decomposition temperature ( -41 O"C) as compared with PES membrane.